2017
DOI: 10.1007/s10286-017-0477-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic effects of vagus nerve stimulation

Abstract: The vagus nerve is responsible for the parasympathetic innervation of the major thoracic and abdominal organs. It also carries sensory afferent fibres from these viscera and reaches different brain structures. These connections have proven useful in the treatment of different diseases. Afferent stimulation of the left vagus nerve is used to treat epilepsy and major depression, and stimulation of the right vagus nerve is being tried for the treatment of heart failure. The device used for the therapy delivers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…When studying interictal HRV before and after implantation, a number of studies reported findings indicating a shift back toward increased parasympathetic activity with VNS; with a similar shift noted in healthy subjects stimulated using transcutaneous VNS . However, multiple other studies failed to find a statistically significant difference before and after VNS treatment . One study reported that VNS actually decreased HRV .…”
Section: Effects Of Treatment On Interictal Hrvmentioning
confidence: 98%
“…When studying interictal HRV before and after implantation, a number of studies reported findings indicating a shift back toward increased parasympathetic activity with VNS; with a similar shift noted in healthy subjects stimulated using transcutaneous VNS . However, multiple other studies failed to find a statistically significant difference before and after VNS treatment . One study reported that VNS actually decreased HRV .…”
Section: Effects Of Treatment On Interictal Hrvmentioning
confidence: 98%
“…These fibers projecting to the NTS will activate and modulate several simple and complex loops and circuitry (i.e., autonomic brainstem and forebrain loops), centrally in a bottom-up mode, and trough up-down reactions, the HPA axis and, in the periphery, immune tracts as the CAP [23][24][25] . Traditionally and otherwise indicated only the left branch of the ABVN is stimulated so that there is less influence on the heart rate, since the left VN innervates the atrioventricular node and the right VN innervates the sinoatrial node controlling the pace-making function of the heart 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, according to anatomical evidence, the effect of left-sided surgery on heart rate may also be more obvious compared with right-sided surgery. (10,24,25) With left-sided surgery, the operation time is slightly longer, but this difference is not signi cant.…”
Section: Discussionmentioning
confidence: 98%